A cross-country study of marketing effectiveness in high-credence services - Angulo-Ruiz, Fernando; Pergelova, Albena; Cheben, Juraj; Angulo-Altamirano, Eladio (My University, 2016)
This research seeks to examine the influence of traditional advertising, Internet marketing, and relational marketing on choice and willingness to recommend across countries with varying levels of the Inglehart–Baker cultural dimensions. In the general model, including four countries, relational, and Internet marketing have a significant and positive effect on choice. In the country-specific models, relational marketing has significant positive effects in Canada, Slovakia, and Peru; traditional advertising only in Peru; and Internet marketing only in Slovakia. None of those activities has an influence on choice in Hungary. Relational marketing and Internet marketing have indirect effects on willingness to recommend through the mediating influence of choice. The study provides evidence of comparative marketing effectiveness in the context of high-credence service across different countries.
Keywords: traditional advertising; Inglehart–Baker cultural dimensions; internet marketing; relational marketing; comparative marketing